Impact of financial stability and growth potential on the investment attractiveness of an organisation - O. E. Astafyeva; Yu. E. Khvostov (Вестник университета, 2025)
In this article, financial stability and its importance in the context of the struggle for access to investment resources are examined as a criterion of investment attractiveness and factor of influence on the growth potential of an enterprise. Based on a number of theoretical provisions, the authors come to the conclusion about the key role of the financial stability in forming the conditions for choosing an enterprise as an investment object. Receiving reliable and substantiated data on the financial stability of an organisation, a potential investor can draw conclusions and forecasts regarding the attractiveness of an investment object, and a potential investment object, in turn, gains the opportunity to take the necessary measures to increase its investment attractiveness. In the current economic realities, a characteristic feature of which is the complication of economic relations and resource maneuvering, it seems necessary to further study the relationship between the investment attractiveness and financial stability and study the influence of the latter on the growth potential in order to form a set of theoretical provisions and develop methods for increasing the economic stability of commercial enterprises, protecting their economic interests as well as for developing measures to enhance competitiveness and competitive advantages in the struggle for investments.